Impact of selenium supplementation on fish antiviral responses: a whole transcriptomic analysis in rainbow trout (Oncorhynchus mykiss) fed supranutritional levels of Sel-Plex®. (December 2016) - Pacitti, D.; Lawan, M.; Feldmann, J.; Sweetman, J.; Wang, T.; Martin, S.; Secombes, C.
Abstract Background Selenium (Se) is required for the synthesis of proteins (selenoproteins) with essential biological functions. Selenoproteins have a crucial role in the maintenance of cellular redox homeostasis in nearly all tissues, and are also involved in thyroid hormone metabolism, inflammation and immunity. Several immune processes rely on Se status and can be compromised if this element is present below the required level. Previous work has supported the notion that when Se is delivered at levels above those deemed to be the minimal required but below toxic concentrations it can have a boosting effect on the organism's immune response. Based on this concept Se-enriched supplements may represent a valuable resource for functional feeds in animal farming, including aquaculture. Results In this study we tested the effects of Se supplemented as Sel-Plex during an immune challenge induced by polyinosinic:polycytidylic acid (poly(I:C)), a pathogen-associated molecular pattern (PAMP) that mimics viral infection. Trout were fed two diets enriched with 1 or 4 mg Se Kg−1 of feed (dry weight) by Sel-Plex addition and a commercial formulation as control. The whole trout transcriptomic response was investigated by microarray and gene ontology analysis, the latter carried out to highlight the biological processes that were influenced by Sel-Plex supplementation in the head kidney (HK) and liver, the main immune and metabolic organs in fish. Overall, Sel-Plex enrichement up to 4 mg Se Kg−1 induced an important response in the trout HK, eliciting an up-regulation of several genes involved in pathways connected with hematopoiesis and immunity. In contrast, a more constrained response was seen in the liver, with lipid metabolism being the main pathway altered by Se supplementation. Upon stimulation with poly(I:C), supplementation of 4 mg Se Kg−1 increased the expression of principal mediators of the antiviral defences, especially IFN-γ, and down-stream molecules involved in the cell-mediated immune response. Conclusions Supplementation of diets with 4 mg Se Kg−1 using Sel-Plex remarkably improved the fish response to viral PAMP stimulation. Sel-Plex, being a highly bioavailable supplement of organic Se, might represent a suitable option for supplementation of fish feeds, to achieve the final aim of improving fish fitness and resistance against immune challenges.